Non-linear phase linking using joined distributed and persistent scatterers. (February 2023) - Mirzaee, Sara; Amelung, Falk; Fattahi, Heresh
Abstract: We describe a python package for nonlinear phase linking of full resolution SAR images using both distributed and persistent scatterers. In the workflow, the first step is to find for each pixel the set of self-similar pixels in order to identify persistent and distributed scatterers. Next the phase linking is performed using the full complex coherence matrix containing the wrapped phase values of each distributed scatterer. Our package uses a hybrid approach consisting of eigenvalue decomposition-based maximum likelihood phase linking and the classic eigenvalue decomposition method. The latter is used for pixels with a non-invertible covariance matrix. A sequential mode achieves computational efficiency. The next step is to unwrap the phase by selecting an optimum unwrapping network of interferograms and invert for the unwrapped phase time-series which is converted to the displacement time-series. We show how the performance of phase linking depends on the temporal correlation behavior using simulations of the coherence matrix. The sequential approaches better retrieve the simulated phases compared to the non-sequential approaches for all temporal coherence models. Phase linking methods retrieve the simulated phase with residuals close to the Cramér–Rao lower bound for coherent seasons where the absolute values of coherence matrix are high and provide a tool for obtaining InSAR measurements over areas with seasonal snowfall. We furthermore show that unwrapping errors propagate differently depending on the unwrapping network. For single-reference networks there is no error propagation, but for sequential networks it compromises the accuracy of the final displacement time-series. Delaunay networks provide an optimum solution in terms of accuracy and precision if there are several years of data with frequent temporal decorrelation or strong seasonal decorrelation. We present applications using Sentinel-1 data in different natural and anthropogenic environments. Highlights: A python package for nonlinear phase linking of SAR images is provided. Phase linking provides InSAR measurements over areas with seasonal snowfall. Unwrapping errors propagate differently depending on the unwrapping network. Delaunay networks are preferred for unwrapping the seasonally decorrelated areas.